SIDE PROJECT FOR THE DISABLED IN GOSTIVAR REGION - Ilyaz, Engin (International Scientific Journal Vision, 2023)
There has been a problem of accessibility since human existence. The formation of a standard design for the disabled is a problem not only in Gostivar but also in many cities around the world. This problem has started to be discussed in recent years with the evaluation of accessibility within the framework of human rights. Determining the factors on this subject is of interest to many different disciplines. However, the role of the architect is very important in the process of applying the required standards. If accessibility is evaluated in all aspects during the design process, there will be no need for additional investment. It will be easier to ensure the accessibility of buildings. However, the adaptation period of the accessibility of existing buildings takes time and requires additional investments. The aim of this study is to investigate the standards of arranging the physical space of the city, which is a public space, in order for the disabled to integrate with the society without encountering any obstacles in the society, and to test these standards with application examples. The main aim is to enable disabled people (without accompanying person) to use urban spaces and buildings independently.